Socialization in the prevention and impact of early marriage in Tanjung Medang Village, Muara Enim Regency - Yusnaini, Yusnaini; Randi, Randi; Malinda, Febrimarani; Istiqoma, Istiqoma; Yulasteriyani, Yulasteriyani; Putra, Decka Pratama; Syafe’i, Akhmad (Universitas Muhammadiyah Magelang, 2025)
The high prevalence of early marriage in Indonesia, exacerbated by suboptimal implementation of regulations, poses significant negative psychological, health, social, and economic impacts on children. This community service activity aimed to increase the knowledge of the community in Tanjung Medang Village, Muara Enim Regency, regarding the impacts and importance of preventing early marriage. Implemented through an initial assessment, comprehensive education on the sociological perspective of early marriage impacts, and a post-intervention evaluation, the program demonstrated a significant increase in knowledge. Pre-test scores, initially at 70%, rose to 97% in the post-test, indicating the effectiveness of the socialization. This enhanced understanding is expected to form a foundation for collective efforts by the community and local government to reduce the rate of early marriage for the future well-being of children.